Collaborative Live Composition with Frankie - Onttonen, Esa (Northeastern University, 2023)
This paper describes a web application being developed for the purpose of collaborative live composition. In this concept, musical information such as pitch sets, chord progressions and textual parameters can be created and communicated in real-time by all members of the group. Primarily designed for tablets, the application aims for high usability values and has been tested and developed with professional jazz musicians. This paper presents the background for the concept of collaborative live composition, along with the main features, design principles and the development process of the application. Finally, the paper describes a concert performance and reflects on the affordances, opportunities, and challenges of the concept.
Keywords: musiikki; muusikot; jazz; säveltäminen